A new monitoring tool CLIP test for progression of oxaliplatin‐induced peripheral neuropathy: A multicenter prospective study. Issue 5 (7th September 2020) - Kamei, Keiko; Ohnishi, Tadashi; Nakata, Ken; Danno, Katsuki; Ohkawa, Atsushi; Miyake, Yasuhiro; Okazaki, Satoshi; Fukunaga, Mutsumi; Toyokawa, Akihiro; Hamada, Tetsuhiro; Shindoh, Junichi; Kanazawa, Akiyoshi
Abstract: Introduction: Oxaliplatin‐induced peripheral neuropathy (OIPN) is a common adverse events that can limit a patient's quality of life during/after chemotherapy. However, no appropriate methods have been established yet for monitoring the risk of progression of OIPN. Methods: A simple assessment tool using gem clips, the CLIP test, was established and its performance in predicting the risk of progression to ≥grade 2 peripheral sensory neuropathy (CTCAE ver. 4.0) was investigated in patients receiving chemotherapy with oxaliplatin. Results: Among 101 patients included in this study, 71 patients developed CTCAE ≥grade 1 peripheral neuropathy (grade 1, n = 67; grade 2, n = 4) at a median of 63 (range, 14–259) days after the start of treatment. Of the 67 patients with grade 1 peripheral neuropathy, 17 showed progression to ≥grade 2 neuropathy after a median interval of 84 (range, 21–246) days. Of these patients, 27 showed a positive result of the CLIP test at a median of 91 (range, 14–224) days, excluding one patient who already showed a positive result of the test at the baseline. Therefore, the risk ratio for the development of CTCAE ≥grade 2 peripheral neuropathy was 8.3 in the patients who showed a positive result on the CLIP test. Multivariate analysis confirmed that a positive results on the CLIP test was significantly correlated with the risk of future development of CTCAE ≥grade 2 peripheral neuropathy (odds ratio, 9.37; P = 0.002). Conclusion: A positive result on the CLIP test predict is predictive of the risk of progression of OIPN during chemotherapy with oxaliplatin.